Analysis and validation of correlation curves between sclerometry and compression tests for the evaluation of compressive strength of concretes - OLIVEIRA,T. M. (2018)
Abstract The present work consists in obtaining correlation curves between compressive tests and sclerometry tests from an extensive experimental program comprising 630 concrete cylindrical samples cast in laboratory, employing materials and methods available in Brazil. The concretes, with compressive strengths ranging from 20~MPa to 50~MPa, were submitted to sclerometry tests and mechanical compressive tests. The results were used to obtain correlation curves. which were adopted in measurements of structural elements molded in a construction site, indicating that the curves provided by the equipment manufacturer are not suitable for the material in study. This is the first stage of a broader study aiming to contribute to the improvement of the Brazilian code regulating the application of the sclerometry to obtain concrete compressive strength.